Contribution of agriculture to national economic development - Oana Camelia Iacob; Ana-Maria Volintiru; Aurel Marin (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 4th Edition of the International Symposium, November 2013, Bucharest, 2013)
At national economic level there is a fierce competitivity, experienced more and more perhaps due to the crisis. Functionality of the economy has been a challenge that many have failed to honor, but at least led us to try to. The chance to succeed was related to everyone's desire to ensure durability.This article is to demonstrate the need to develop agricultural policies in rural areas, but measures to encourage private initiatives are also included in order to satisfy completion of measures on the farm and to provide alternative employment opportunities for the rural population. Improvement of the poverty status of the population employed in agriculture, development of entrepreneurial initiative and increasing economic competitiveness leads to a harmonious development.
Keywords: 330; agricultural policy; productivity; rural development